Outcomes of Total Hip Replacement in Limbs Affected by Poliomyelitis. Issue 2 (March 2017) - Faldini, Cesare; De Fine, Marcello; Di Martino, Alberto; Fabbri, Daniele; Borghi, Raffaele; Chehrassan, Mohammadreza; Traina, Francesco
Introduction: The outcomes of total hip replacement in patients suffering from residual poliomyelitis are poorly covered in the literature. In this retrospective study we posed the question of whether total hip replacement performed for degenerative hip diseases in limbs with residual poliomyelitis could determine satisfactory mid-term clinical and radiographic results, with a reasonable complication rate. Methods: A retrospective study was carried out to assess the results of 14 total hip replacements performed on 14 patients with residual poliomyelitis on the involved limb from June 1999 to September 2011. Average age at the time of surgery was 51 years (range 26-66 years). Mean duration of follow-up was 92 months (range 52-156 months). Surgery was performed through a direct lateral approach on all hips. All but one were cementless implants. Results: 2 implants failed, 1 due to traumatic acetabular fracture 6 days after surgery, and 1 due to aseptic cup loosening 13 years after surgery. Surgery was uneventful in all patients except 1 (7%), who experienced a transient sensory sciatic nerve palsy. At the latest follow up Harris Hip Score was 83.3 (range 72-91) with a marked improvement when compared to preoperative score (average 52, range 32-78). No dislocations had occurred. Conclusions: Total hip replacement can be considered a feasible option for hip osteoarthritis in patients with limbs affected by residual poliomyelitis. Longer follow-up studies are needed to assess the effectiveness of unconstrained total hip replacement in polio patients.